2020
DOI: 10.1002/jbt.22654
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long‐term treatment with a mixture of pyrethroids on the expression of genes that govern male germ cell production in rats

Abstract: Humans are exposed to pyrethroid‐based pesticides through agricultural produce. In this study, male Wistar rats were orally treated for 9 to 12 months with a mixture of pyrethroids that is equivalent to one‐fifth (high dose; HD) or one‐twenty fifth (low dose; LD) of the amount of pyrethroids present in the cereals and rice consumed by an average Indian. In rats treated for 9 months, the spermatogenesis‐associated genes Abp, Ar, Cd9, Dax1, Dazap1, Ddx3y, Gdnf, Gfra1, Grth, Inhb, Ovol1, P1, Plzf, Pygo2, Scf, Tgf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
(70 reference statements)
1
6
0
Order By: Relevance
“…Sirt1, a member of the sirtuin family, is an important regulator of various biological processes [ 33 ], while IL10 is a critical anti-inflammatory cytokine produced by multiple cell types [ 34 ]. A previous study confirmed that CMN decreased the mRNA expression levels of Sirt1 in the germ cells of male rats [ 35 ]. However, CMN was also found to increase the mRNA expression levels of IL10 in rat striatum, which is contrary to results of the present study [ 36 ].…”
Section: Discussionsupporting
confidence: 72%
“…Sirt1, a member of the sirtuin family, is an important regulator of various biological processes [ 33 ], while IL10 is a critical anti-inflammatory cytokine produced by multiple cell types [ 34 ]. A previous study confirmed that CMN decreased the mRNA expression levels of Sirt1 in the germ cells of male rats [ 35 ]. However, CMN was also found to increase the mRNA expression levels of IL10 in rat striatum, which is contrary to results of the present study [ 36 ].…”
Section: Discussionsupporting
confidence: 72%
“…[ 69 ] Imbalance in the oxidant to antioxidant status associated with damage to the anatomical architecture of male reproductive organs due to exposure to a mixture of pyrethroids was reported by us earlier. [ 23–25,70–72 ] Histological alterations associated with oxidative stress in the male reproductive organs of deltamethrin, bifenthrin, permethrin, beta‐cypermethrin and cypermethrin treated rats [ 19,73–75 ] are reported in the recent years. Results of this study provide strong evidence that exposure to a mixture of pyrethroids at doses equivalent to that present in agricultural food products consumed on a daily basis potentially affect the male reproductive system function.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the physiological, biochemical, and genotoxic effects in different organs of rats of a mixture of pyrethroids at doses relevant to the amounts that are present in the amount of rice and vegetables consumed by an average Indian. [23][24][25] In this study, to further explore the effects of pyrethroids on the functioning of various organ systems (hepatic, renal, and male reproductive) at biochemical level, we treated rats with a mixture of pyrethroids (that are found to be present in rice and vegetables available at Indian markets) at doses that are equivalent to residual levels of the present in the quantity of rice and vegetables consumed by an average Indian. Thus, this study reflects the real-time settings of human exposure.…”
mentioning
confidence: 99%
“…Structural modifications of pyrethrins aimed at increasing stability and insecticidal properties produced the first synthetic pyrethroid insecticides, the most successful of which being allethrin (Figure 1) invented at the United States Department of Agriculture in 1949. It was followed in 1963 by tetramethrin (Sumitomo Chemical), and permethrin (Rothamsted Experimental Station) in 1973… Today, 42 different pyrethroid insecticides with varying chemical structure or relative composition of stereoisomers are available [21] . Pyrethroids are among the most used insecticides, accounting for about 16 % of the worldwide insecticide market [22] .…”
Section: Voltage‐gated Sodium Channelsmentioning
confidence: 99%